2020
DOI: 10.1111/odi.13731
|View full text |Cite
|
Sign up to set email alerts
|

Oral health education and promotion in special needs children: Systematic review and meta‐analysis

Abstract: Intellectual disability (ID) is characterised by significant limitations in both intellectual functioning and adaptive behaviours (Schalock et al., 2010). Its onset occurs during the developmental period (American Psychiatric Association, 2013), before 18 years of age (Schalock et al., 2010), while the classification for severity (mild, moderate, severe or profound) reflects the level of support required for functioning (American Psychiatric Association, 2013).Developmental disability is "a severe, long-term d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 49 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…6,10,24 A recent study evaluating oral health utilization in children with Rett's syndrome found that mothers who had only completed high school education visited private dental clinics less often compared with those who had completed a tertiary degree. 31 However, this could possibly reinforce the previously stated belief that parents may be accessing more public sector services and care provided through hospitals alongside multi-disciplinary medical management. [27][28][29][30] Findings from this study also focus on the role of household income towards dental attendance patterns.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…6,10,24 A recent study evaluating oral health utilization in children with Rett's syndrome found that mothers who had only completed high school education visited private dental clinics less often compared with those who had completed a tertiary degree. 31 However, this could possibly reinforce the previously stated belief that parents may be accessing more public sector services and care provided through hospitals alongside multi-disciplinary medical management. [27][28][29][30] Findings from this study also focus on the role of household income towards dental attendance patterns.…”
Section: Discussionmentioning
confidence: 77%
“…One study of Australian adults revealed that those with disabilities living in regional communities had a lower dental attendance rate compared with those living in major cities 19 . It was suggested that the lack of appropriate transport and associated costs can influence regular attendance for individuals living regionally 19,31 . This barrier is likely to be intensified for parents taking care of children with disabilities as medical costs and balancing appointments with work can all undermine regular dental attendance significantly 2,6,8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations